Analysis of the complete organellar genomes of the rockweed Fucus spiralis (Fucaceae, Phaeophyceae) supports its infraspecific recognition as Fucus vesiculosus var. spiralis. Issue 2 (3rd July 2018) - Alvarez, Alejandra; Anaya, Juan; Arellano, Bibiana; Bartlebaugh, Austin; Capurro, Michael C.; Carrillo, Adriana; Chacon, Isaiah R.; Cordova, Lizbeth; Corral, Bethany; DaSilva, Melina; Del Valle, Giselle; Diaz, Alexis; et al.
Abstract: Fucus spiralis L. is a broadly distributed monoecious intertidal seaweed. The specific status of F. spiralis however is debatable. Here, we contribute to the bioinformatics and systematics of F. spiralis by analysing the complete mitochondrial and plastid genomes of a specimen from California, U.S.A. The F. spiralis mitogenome is 36, 396 base pairs (bp) in length and contains 67 genes, and the plastid genome is 125, 066 bp in length and contains 171 genes. The F. spiralis genomes are 99.7% and 99.8% similar in nucleotide sequence to F. vesiculosus, and support the revised classification of F. spiralis to Fucus vesiculosus var. spiralis .